2022
DOI: 10.1038/s41467-022-30126-9
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial GxGxE CRISPR screen identifies SLC25A39 in mitochondrial glutathione transport linking iron homeostasis to OXPHOS

Abstract: The SLC25 carrier family consists of 53 transporters that shuttle nutrients and co-factors across mitochondrial membranes. The family is highly redundant and their transport activities coupled to metabolic state. Here, we use a pooled, dual CRISPR screening strategy that knocks out pairs of transporters in four metabolic states — glucose, galactose, OXPHOS inhibition, and absence of pyruvate — designed to unmask the inter-dependence of these genes. In total, we screen 63 genes in four metabolic states, corresp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 64 publications
2
42
1
Order By: Relevance
“…S13B) in a MTCH2 knockout background had an additive effect on biogenesis of many mitochondrial TAs. This result is consistent with recent pair-wise genetic interaction maps that have found a synthetic lethal relationship between MTCH1 and 2 (28), and the fact that MTCH1 was also a statistically significant hit in our genome-wide screen (fig. S12; S13C).…”
Section: Main Textsupporting
confidence: 93%
“…S13B) in a MTCH2 knockout background had an additive effect on biogenesis of many mitochondrial TAs. This result is consistent with recent pair-wise genetic interaction maps that have found a synthetic lethal relationship between MTCH1 and 2 (28), and the fact that MTCH1 was also a statistically significant hit in our genome-wide screen (fig. S12; S13C).…”
Section: Main Textsupporting
confidence: 93%
“…Likewise, simply changing the composition of the medium can induce large-scale metabolic alterations in cultured cells, implying that nutrient availability is a major factor dictating metabolic phenotypes 65,66 . These context-specific preferences can translate into altered metabolic demands: a subset of metabolic genes exhibit conditional essentiality depending on exogenous nutrient availability 67,68 . Somewhat surprisingly, therefore, genetic screens revealed that pancreatic cancer cells grown in 2D in vitro or as tumours in mice exhibited overall strikingly similar requirements for metabolic genes 69,70 .…”
Section: Supporting Aberrant Cell Proliferationmentioning
confidence: 99%
“…This result is consistent with our genome-wide screen (fig. S17C) and the synthetic lethal relationship between MTCH1 and 2 ( 21 ). We therefore propose that MTCH1 and 2 are the founding members of a distinctive class of membrane protein insertases that exploit the SLC25 transporter fold (fig.…”
mentioning
confidence: 99%